A note on the global attractivity of a discrete model of nicholson's blowflies - B. G. Zhang; H. X. Xu (Discrete Dynamics in Nature and Society)
In this paper, we further study the global attractivity of the positive equilibrium of the discrete Nicholson's blowflies model Nn+1−Nn=−δNn+pNn−ke−aNn−k,        n=0,1,2,…. We obtain a new criterion for the positive equilibrium N∗ to be a global attractor, which improve the corresponding results obtained by So and Yu (J. Math. Anal. Appl. 193 (1995), 233–244).